2020
DOI: 10.1039/d0ra06278b
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal conversion of SiO2@Au nanoparticles mediated by surface morphology of gold cluster layer

Abstract: We manipulate the surface morphology of gold clusters on SiO2@Au nanoparticle and found that macroscopic photothermal conversions of different nanoparticle dispersions are significantly affected by nanoscale differences of gold cluster morphologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…A similar relationship between energy per pulse and OA signal intensity at high fluence levels was shown to be produced for gold-wrapped carbon nanotubes and carbon nanotubes. , It was also previously reported that the photodamage threshold for a single Au sphere of 20–50 nm lies in the range 33–80 mJ/cm 2 for 532 nm excitation with a nanosecond pulsed laser . However, the behavior of gold clusters is more complicated due to high plasmonic coupling between nanoparticles, which could lead to an increase in the light-to-heat conversion and a consequent shift of the energy threshold to a lower range. No significant nonlinear effects as a function of fluence were observed in OA signals collected with the OAT system for fluence levels used in vivo (Figure S3d). Note that such signals correspond to a suspension of microparticles in PBS that may slightly move during data acquisition.…”
Section: Resultssupporting
confidence: 72%
“…A similar relationship between energy per pulse and OA signal intensity at high fluence levels was shown to be produced for gold-wrapped carbon nanotubes and carbon nanotubes. , It was also previously reported that the photodamage threshold for a single Au sphere of 20–50 nm lies in the range 33–80 mJ/cm 2 for 532 nm excitation with a nanosecond pulsed laser . However, the behavior of gold clusters is more complicated due to high plasmonic coupling between nanoparticles, which could lead to an increase in the light-to-heat conversion and a consequent shift of the energy threshold to a lower range. No significant nonlinear effects as a function of fluence were observed in OA signals collected with the OAT system for fluence levels used in vivo (Figure S3d). Note that such signals correspond to a suspension of microparticles in PBS that may slightly move during data acquisition.…”
Section: Resultssupporting
confidence: 72%
“…Thus, we obtained the core@shell structure of PBA@SiO 2 (Figures S3 and S4, Supporting Information). In order to introduce the function of glucose consumption [ 24 ] (glucose+normalO2AuNPsgluconic acid+normalH2normalO2) and photothermal conversion [ 25,26 ] from gold nanoparticles, the exchange of the ligand with 3‐aminopropyltriethoxysilane and a redox reaction with HAuCl 4 further resulted in the formation of PBA@SiO 2 ‐Au NPs. These PBA@SiO 2 ‐Au NPs showed a distinctive hierarchical hybrid structure and had a diameter of 142.4 ± 4.6 nm.…”
Section: Resultsmentioning
confidence: 99%
“…We focused on light irradiation combination with metal nanoparticles since no mechanism of resistance has yet been identified. The photothermal conversion mediated by metal nanoparticles ( Kim et al, 2019 ; Yang et al, 2020 ) triggers a local surge in temperature ( Supplementary Table 4 ) that impacts bacteria cells’ viability and the stability of the extracellular matrix, decreasing its thickness ( Jo and Kim, 2013 ; Wang et al, 2019 ; Beckwith et al, 2020 ; Pinel et al, 2021 ). Previous studies have shown that the structure and the integrity of bacterial biofilms could be disrupted at higher temperatures ( Ibelli et al, 2018 ), thus decreasing the barrier limiting antimicrobial diffusion to different layers of the biofilm.…”
Section: Resultsmentioning
confidence: 99%